The Effects of Interactive Virtual Reality in Patients with Chronic Musculoskeletal Disorders: A Systematic Review and Meta-Analysis - Kantha, Phunsuk; Lin, Jiu-Jenq; Hsu, Wei-Li (Games for health, 2023)
Interactive virtual reality (iVR) has been widely used for treatment purposes in patients with chronic musculoskeletal disorders. However, no consensus has been reached on the effects of iVR on pain, psychological distress, and functional disability. Therefore, this study aims to investigate the effects of iVR on pain, psychological distress, and functional disability in patients with chronic musculoskeletal disorders compared with no rehabilitation and conventional rehabilitation. Five electronic databases (PubMed, Cochrane CENTRAL, Scopus, EMBASE, and Web of Science) were searched from January 2016 to December 2021. All randomized controlled trials using iVR for treating pain, psychological distress, and functional disability in patients with chronic musculoskeletal disorders were included. A subgroup analysis was conducted to compare the effects of nonimmersive and immersive types of iVR on the outcomes of interest. Our study provides good quality evidence that iVR reduced overall pain by 9.28 points as compared with no rehabilitation and by 8.09 points as compared with conventional rehabilitation. In the subgroup analysis, nonimmersive iVR showed a reduction in psychological distress (standardized mean differences = -0.35) as compared with no rehabilitation. However, no statistically significant difference in the outcomes existed between nonimmersive and immersive iVR. Furthermore, there were no statistically significant differences in the outcomes of functional disability. iVR is recommended for reducing pain intensity more than no rehabilitation or conventional rehabilitation. Meanwhile, nonimmersive iVR has been proposed for psychological distress improvement, with effects similar to those of conventional rehabilitation. However, iVR may not be an effective intervention in the case of functional disability.